Cover Image, Volume 22, Issue 7. Issue 7 (19th June 2020) - Schernthaner, Guntram; Groop, Per‐Henrik; Kalra, Philip A.; Ronco, Claudio; Taal, Maarten W.
Abstract : The outside front cover image is based on the Review Article SGLT‐2 Inhibitor Renal Outcome Modification in Type‐2 Diabetes: Evidence from Studies in Patients with High or Low Renal Risk by Guntram Schernthaner, PHILIP A KALRA, M Taal et al., https://doi.org/10.1111/dom.13994 .